S117 Work-related symptoms in laboratory animal workers. (15th November 2016) - Feary, J; Canizales, J; Fitzgerald, C; Fitzgerald, B; Schofield, S; Jones, M; Cullinan, P
Abstract : Introduction: Laboratory animal workers frequently report ocular, nasal and respiratory symptoms which occur in the workplace and improve away from work. A proportion of these will be sensitised to animal proteins on the basis of skin prick tests (SPTs) or serum specific IgE testing and will have laboratory animal allergy. The remainder will have work-related symptoms due to other (unknown) causes. Methods: We performed a cross-sectional study (SPIRAL (Safe Practice In Reducing Allery in Laboratories)) of laboratory animal workers exposed to mice across six UK research institutions. Participants completed a self-administered questionnaire, which included detailed questions about symptoms, and underwent SPT to common aeroallergens and mouse epithelium, and specific IgE testing to mouse proteins (epithelium and urine). Those participants reporting ocular, nasal or respiratory symptoms which were worse at work were compared with those with no association between their symptoms and work. Results: 685 laboratory workers were recruited (response rate 88%). 187 (28%) reported at least one symptom and of these, 45% (n = 85) were work-related (WR). 56/105 (53%) reported work-related conjunctivitis; 67/156 (43%) reported WR nasal symptoms and 22/44 (50%) reported WR respiratory symptoms. There were no differences between the two groups in sex, smoking status, atopy to a common aeroallergen or job title. Those with at least one WR symptom were significantly more likely to be sensitisied to mouse proteins (32 (37.7%) vs 10 (9.8%) p < 0.001 (Table). WR symptoms were significantly more common in those working with mice housed in open cages compared with those housed in Individual Ventilated Cages (IVCs) Prevalence of sensitisation to a common aeroallergen was similar in both groups. Conclusion: In this large study population, prevalence of WR symptoms is reasonably high in all laboratory animal workers and is attributable to mouse allergy in around 50% of cases, consistent with other previous studies. Symptoms are less prominent in people working with IVCs compared with conventional open cages. Exposure to airborne endotoxin may be a cause for nasal and respiratory symptoms on exposure to mice in non-mouse sensitised animal workers. Measurement of exposure to endotoxin levels in these workers is in progress.